Monocarboxylate Transporters 1 and 4 and MTCO1 in Gastric Cancer - Eskuri, Maarit (Cancers (Basel), 2021)
SIMPLE SUMMARY: The expression of monocarboxylate transporters (MCTs) are reported in a variety of cancers and suggested as a therapeutic target for cancer treatment. However, previous study results in gastric cancer are contradictory. In this study, we evaluated the expression of MCT1, MCT4, and Mitochondrial cytochrome c oxidase (MTCO1) and their association with clinicopathological parameters and prognostic significance in a cohort of 568 surgically treated gastric cancer patients. The results suggest that monocarboxylate transporters and MTCO1 are associated with gastric cancer progression but have no independent prognostic relevance. ABSTRACT: Background: Monocarboxylate transporters (MCTs) appear to play an important role in tumor development and aggressiveness. The present study aimed to evaluate associations between cytoplasmic MCT1, MCT4, and mitochondrial cytochrome c oxidase (MTCO1) expression and clinicopathological variables or survival in gastric cancer. Material and methods: A total of 568 gastric adenocarcinoma patients were included in this retrospective cohort study. Protein expressions were detected by immunohistochemical staining. The patients were divided into low expression and high expression groups by median value. The Chi-squared test was used to compare categorical variables. The T-test was used to compare continuous variables. Expressions were analyzed in relation to 5-year survival and overall survival. Cox regression provided HRs and 95% CIs, adjusted for confounders. Results: High cytoplasmic MCT1 expression was associated statistically significantly with higher T-class (p = 0.020). High cytoplasmic MCT4 expression was associated statistically significantly with positive lymph node status (p = 0.005) and was more common in Lauren’s intestinal type (p < 0.001). Low cytoplasmic MTCO1 expression was associated statistically significantly with positive distant metastases (p = 0.030), and high cytoplasmic MTCO1 expression was associated more often with intestinal type (p = 0.044). However, MCT1, MCT4, and MTCO1 were not associated with survival. Conclusions: Monocarboxylate receptors seem to be associated with gastric cancer progression but have no independent prognostic relevance.